Epidemiology of Soil Transmitted Helminthiasis in Depok, West Java - Wita Mulya Rosalina (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2021)
Soil transmitted Helminthiasis (STH) is one of the infectious diseases which is still a health problem in Indonesia, because it is still contagious in most parts of Indonesia. This disease can cause significant losses for sufferers such as decreasing health, nutrition, intelligence, and productivity. This study aims to determine the prevalence of helminthiasis in Depok City in 2019. This study used a cross sectional design which was carried out in 30 elementary schools in Depok City, West Java. The sample of selected grade 3 - 5 primary school students was taken by the Two Stage Cluster Sampling method. A total of 315 student faecal samples were examined by the Kato-Katz and 524 questionnaires about knowledge, environmental sanitation and personal hygiene were collected. The result of this survey is that the prevalence of worms in Depok City in 2019 is 0.32. With this result, the recommendation is that there is no need to give worm drug treatment in this region anymore. Based on the results of the questionnaire, knowledge about the symptoms and methods of prevention was quite good, personal hygiene also mostly in good criteria however there were still 88.2% who had not washed their hands with soap before meals, and 94.1% of children had not washed their hands with soap after defecation. Although the prevalence of helminthiasis in Depok City is relatively low, there is still a need to increase awareness about the behavior of washing hands with soap before eating and after defecation